The Influence of Organizational Citizenship Behavior on Employee Performance with Teamwork as an Intervening Variable at BPJS Employment Tanjung Morawa Branch - Leider Tirta; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research aims to examine the influence of organizational citizenship behavior on employee performance with teamwork as an intervening variable at BPJS Employment, Tanjung Morawa Branch. This type of research uses quantitative, this research was conducted at Bpjs Employment Tanjung Morawa Branch, the population used was 50 employees, 33 Tanjung Morawa, 8 Tinggi cliffs, Serdang Bedagai 9. The sample used was the entire population of 50 employees with a saturated sample being the sampling technique. The data sources used are primary data sources and data collection by distributing questionnaires. This research model uses phat analysis, and the measuring tool is the smart PLS application version 3.3.3. The results of this research are as follows: Organizational Citizenship Behavior has a positive and significant effect on Employee Performance with an original sample value of 0.743 and ap value of 0.000. Organizational Citizenship Behavior has a positive and significant effect on Teamwork with an original sample value of 0.906 and ap value of 0.000. Teamwork has a positive and insignificant effect on employee performance with an original sample value of 0.127 and ap value of 0.536. Organizational Citizenship Behavior has a positive and insignificant effect on Employee Performance through Teamwork indirectly with an original sample value of 0.115 and a P value of 0.540.